Celiac disease presenting as transient intussusception in two 3-year-olds - Tóth, Gergely (Journal of Advanced Pediatrics and Child Health, 2023)
Although intussusception occurs in children and adults with celiac disease, it is a relatively uncommon symptom. Even more rare is the occurrence of intussusception as the presenting symptom of the disease. In the two cases we report here, transient intussusception, occurring at three years of age, was the first and only physical sign of celiac disease, and lead to a timely diagnosis by immunoserology and histology, followed by implementation of a gluten-free diet before sequelae such as significant anemia or Failure to Thrive (FTT) developed. In both cases, neither immunoserological nor physical signs of disease were present at the follow-up examination after 6 months on a gluten-free diet. In addition, genetic screening of the patients’ families revealed HLA-DQ2 positivity in two cases, leading to the additional diagnosis of celiac disease in the pregnant mother of one of the patients.